2016
DOI: 10.4236/me.2016.74055
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Risk Management in the US Banking Sector Following the Financial Crisis

Abstract: Purpose: The purpose of this paper is to investigate the effect of the financial crisis on the management of risk in the largest US banks. Design/Methodology/Approach: Levels of risk exposure, risk consequences and risk management were examined using a content analysis of the 10-K annual reports form of a sample of 59 largest U.S. banks. Paired-t-test, along with frequency analysis of the disclosures of 15 banking risks was used to test our research hypotheses. Findings: We found that the subprime financial cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The recent financial crisis (Gorton, 2009;Zéghal & El Aoun, 2016) revealed that banks, especially these large and complex banks, are opaque to be monitored by regulators. As a result, regulators are now increasingly relying on supervisory risk assessment tools to learn about bank-specific risk exposures and capital adequacy.…”
Section: Introductionmentioning
confidence: 99%
“…The recent financial crisis (Gorton, 2009;Zéghal & El Aoun, 2016) revealed that banks, especially these large and complex banks, are opaque to be monitored by regulators. As a result, regulators are now increasingly relying on supervisory risk assessment tools to learn about bank-specific risk exposures and capital adequacy.…”
Section: Introductionmentioning
confidence: 99%